Utilisation of decanter cake from palm oil milling plant as new substrate for the production of bio-oil through catalytic vacuum pyrolysis - Nugroho, Dewayanto (2015)
The present study was carried out to investigate the potential of palm oil decanter cake (PDC) as the new substrate for bio-oil production. Conversion of PDC into bio-oil was conducted through vacuum pyrolysis. Maximum bio-oil yield was 22.12% obtained at pyrolysis temperature of 500 ºC. The chemical characterisation of bio-oil was studied using 1H-NMR, FTIR, CHNS analyzer and GC–MS. The other properties like pH, calorific value and thermal volatilization were also determined. For comparison purpose, pyrolysis of palm kernel shell (PKS) was also conducted using the same method in PDC pyrolysis. The results indicate PDC bio-oil characteristic is better than that of PKS bio-oil in terms of lower oxygen content, higher pH and heating value. The pH value of PDC recorded to be 6.38, which is found to be higher as compared to that of other bio-oils. The calorific value of PDC bio-oil was found to be 36.79 MJ/kg, which is slightly lower than that of conventional liquid fuel such as gasoline and diesel fuel and much higher than that of bio-oils derived from lignocellulosic biomass. Fatty acid derived from decomposition of triglycerides dominated the composition of PDC bio-oils, while phenolic compounds were prominently found in PKS bio-oil. Effect of catalyst addition was studied by using single and dual stages of pyrolysis reactor. Single stage catalytic pyrolysis was conducted by mixing the catalyst with the biomass in a certain ratio prior to the experiment and was placed into the vacuum pyrolysis reactor. Catalytic reaction reduced the yield of PDC bio-oils, from 22.12 wt% to 15.22 – 17.09 wt%. Catalytic activity of CaO and MgO enhanced the formation of methyl ester through the transesterification reaction of fatty acid, which was produced from decomposition of PDC. Generally, the oxygen content was decreased in presence of catalysts. H-ZSM5 provides better oxygen content reduction than that of other catalysts, both for PDC and PKS. The presence of catalysts slightly affected the pH value and HHV of bio-oils. Dual stage catalytic pyrolysis was conducted by placing the catalysts separately into a catalyst reactor bed to catalyse the upgrading of pyrolytic vapor occurred. Less bio-oil were produced by dual stages catalytic pyrolysis. However, the ratio of O/C decreased while the calorific value slightly increased in dual stage pyrolysis. Bio-oils produced from PDC catalytic pyrolysis has relatively high calorific value than that of other bio-oils, and comparable to the HHV of petroleum fuels. Therefore, PDC bio-oil can be considered as potential alternative fuel. Kinetic studies of PDC pyrolysis were conducted by using thermogravimetry data. Coats-Redfern approach was employed to describe the kinetic model of the PDC thermal decomposition. It was found that the major decomposition of PDC occurred at 220 – 530 °C, represent for decomposition of hemicellulose, cellulose, lignin and triglycerides contained in PDC. Two stages of reaction were identified, first stage at 220 – 300 °C obeyed first order kinetic model, while second stage at 300 – 530 °C was best fit for second order kinetic model. Triglyceride decomposition dominated the whole pyrolysis reaction. As conclusion, decanter cake from palm oil milling plant has potential to be utilised as new substrate for the production of bio-oil through catalytic vacuum pyrolysis